(untitled) (Homoeopathy for All, 2025)
Piles are another term for haemorrhoids. Haemorrhoids are collections of inflamed tissue in the anal canal. They contain blood vessels, support tissue, muscle, and elastic fibers. Piles are certainly one of the commonest ailments that afflict mankind. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.